2020
DOI: 10.1007/s11135-020-01028-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 in E-learning on higher education institution students: the group comparison between male and female

Abstract: In response to the emerging and ever solution to the COVID-19 outbreak. This study proposes a theoretical framework based on literature and model to determined E-learning portal success. The study compared males and females to E-learning portal usage. The study objective is to check the difference between male and female E-learning portals’ accessibility among the students’ perspective. The study included service quality, system quality, information quality, user satisfaction, system use, and E-learning portal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
385
2
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(431 citation statements)
references
References 50 publications
34
385
2
10
Order By: Relevance
“…T he study found that some teachers have no confidence to use technology therefore they were reluctant and unable to motivate their students for blended learning. This finding is aligned with the study of (16,17) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…T he study found that some teachers have no confidence to use technology therefore they were reluctant and unable to motivate their students for blended learning. This finding is aligned with the study of (16,17) .…”
Section: Discussionsupporting
confidence: 90%
“…Students enjoy their work and spend more time on studies compared to traditional mode. Blended learning is intensely encouraged by the universities and provides impending benefits to instructors and students (15,16) .…”
Section: Discussionmentioning
confidence: 99%
“…Study findings is supported by Study done to assess the availability of international standards for education technology (ISTE) the difference of both from gender, specialization, and the academic level in the availability of standards for (458) students, the results indicated that there were no differences to the degree of availability of criteria for the difference in gender or specialization (Hakami, 2019). In another point, the study result is unsupported by Shahzad et al(2020c). The study objective is to check the difference between male and female E-learning portals' accessibility among the students' perspective.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is very rare research available that identified the firm's performance with government support and innovation, particularly in developing countries [76]. However, previous studies have also used government support in innovation usage like e-marketing, e-government, e-banking, and e-learning [60,[77][78][79]. Thus, all the above-discussed issues are causing a direct or indirect effect on SMEs' performance, which needs to be tested with the RBV theory.…”
Section: Government Support Use Of E-commerce and Firm Performancementioning
confidence: 99%